The relationship between the S-wave in lead 1 and recurrence of RVOT PVC ablation - Güneş, Hacı Murat; Demir, Gültekin Günhan; Karaca, Oğuz; Kızılırmak Yılmaz, Filiz; İbişoğlu, Ersin; Gökdeniz, Tayyar; Omaygenç, Mehmet Onur; Güler, Ekrem; Babur Güler, Gamze; Savur, Ümeyir; Çakal, Beytullah; Barutçu, İrfan; et al. (Churchill Livingstone Inc Medical Publishers, 2018)
Background: Radiofrequency catheter ablation (CA) is a common non-pharmacological treatment option for ventricular premature contractions (PVCs) originating from right ventricular outflow tract (RVOT). In this study, we aimed to investigate the relationship between recurrence after CA for RVOT-PVC and S-wave in lead 1 that was shown to be associated with RVOT depolarization. Methodology: A total of 104 patients who were referred to our clinic for CA for idiopathic RVOT-PVC between 2012 and 2015 years were enrolled. All ECG parameters were measured before and after the ablation procedure. Results: Ablation was successful in 100 patients (96,1%). These patients with successful ablation were followed for a mean duration of 1078 days. 13 patients (13%) had recurrence. Univariate logistic regression analysis revealed age (odds ratio: 1.916, p:0,012), presence of post-procedural S1 (odds ratio:1.040 p:0,028), post-procedural S1 area (oddsratio:1.023 p:0,041), AS] area (odds ratio:1.242 p:0,004) as predictors for recurrence. Multivariate logistic regression analysis detected age (odds ratio:1.053 p:0,032) and AS] area (odds ratio:0.701 p:0,009) as predictors for recurrence. Conclusion: Radiofrequency CA for RVOT-PVC can be performed with high procedural success and low complication rates. Age and Delta S1 area might be helpful for prediction of recurrence after CA.
WOS: 000434104700038
PubMed ID: 29277286
Keywords: S-wave in Lead 1; RVOT-PVC Ablation; Recurrence